2016
DOI: 10.20944/preprints201612.0150.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Addressing Environmental Health Problems in Ogoniland through Implementation of United Nations Environmental Program Recommendations: Environmental Management Strategies

Abstract: In August 4 2011, United Nations Environmental Program (UNEP) submitted an unprecedented, scientific, groundbreaking Environmental Assessment Report (EAR) of Ogoniland, to the Nigerian government. This was the outcome of a 14–month intensive evaluation of the extent of pollution. It was intended that UNEP’s recommendations would be implemented to restore the devastated environment, on the one hand, and on the other, counteract the numerous environmental health issues that have for decades, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…This will thus enhance the economic well being of the Ogonis. This is because the Ogonis are predominantly farmers and traditional fishers (Yakubu, 2017). The Ogonis as a local community have been faced with displacement, dispossession and exposure to risk (Howitt, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…This will thus enhance the economic well being of the Ogonis. This is because the Ogonis are predominantly farmers and traditional fishers (Yakubu, 2017). The Ogonis as a local community have been faced with displacement, dispossession and exposure to risk (Howitt, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Clinton et al (2009) also evaluated, analyzed, and indicated that the total petroleum hydrocarbons (TPHCs) in a water sample at the well-head stations, in Niger Delta were above the 10 mg/L tolerance level recommended by the Federal Ministry of Environment in Nigeria. Clinton et al (2009) and Yakubu (2017) described Total Petroleum Hydrocarbons [TPHCs] as the mixture of organic compounds found or derived from crude oil that have the ability to be toxic. These compounds have limited solubility thereby forming individual liquid phases known as non-aqueous phase liquids [NAPLs].…”
Section: Introductionmentioning
confidence: 99%